Teaching bone marrow procedures at pelvic and sternal sites: a high fidelity anatomy simulation - VanderMeulen, Heather; Laureano, Marissa; Hu, George; Lim, Wendy; Ross, Catherine; Wainman, Bruce; Zeller, Michelle P (Canadian Medical Education Journal / Revue canadienne de l'éducation médicale)

(untitled) (Canadian Medical Education Journal, 2021)
Implication Statement: The bone marrow aspirate and biopsy procedure are fundamental to the diagnosis of many hematologic pathologies. We describe a hands-on, anatomy-based workshop that allows learners to practice bone marrow procedures on cadavers. Notably, participants learned how to perform sternal aspirates: a procedure rarely performed in real-life practice. Learners valued the experience and described increased comfort with the procedure after the workshop. This workshop provides a valuable opportunity for trainees to learn a procedural skill in a safe, high fidelity environment. Given its hands-on nature, residency training programs could also adapt it for direct observation and trainee assessment.